Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
Объяснение:
Ca + H2 = CaH2
Ca(0) -2e = Ca(+2) 1 ок-ие
в-ль
H2(0) +2e = 2H(-) 1 в-ие
ок-ль
CaH2 + H2O = Ca(OH)2 + H2
Ca(OH)2 + CO2 = CaCO3↓+ H2O
CaCO3 + 2HCl = CaCl2 + CO2↑ + H2O
CaCO3 + 2H(+) + 2Cl(-) = Ca(2+) + 2Cl(-) + CO2↑ + H2O
CaCO3 + 2H(+) = Ca(2+) + CO2↑ + H2O
3CaCl2 + 2H3PO4 = Ca3(PO4)2↓ + 6HCl
3Ca(2+) + 6Cl(-) + 6H(+) + 2PO4(3-) = Ca3(PO4)2↓ + 6H(+) + 6Cl(-)
3Ca(2+) + 2PO4(3-) = Ca3(PO4)2↓
2Ca + O2 = 2CaO
Ca(0) -2e = Ca(+2) 2 ок-ие
в-ль
O2(0) +4e = 2O(-2) 1 в-ие
ок-ль
CaO + H2O = Ca(OH)2
CaCO3 -> CaO + CO2
CaO + 2HCl = CaCl2 + H2O
CaO + 2H(+) + 2Cl(-) = Ca(2+) + 2Cl(-) + H2O
CaO + 2H(+) = Ca(2+) + H2O